Autoimmune Thyroid Disease and Breast Cancer Prognosis - (:unkn) unknown (AVES, 2015)
Objective: The association of breast cancer and thyroid autoimmunity has been suggested by many studies in the literature, but the causality still needed to be proven. With this study we aimed to search the correlation between thyroid autoimmunity and breast cancer prognostic factors. Materials and Methods: To this prospective cohort study 200 consecutive breast cancer patients, who were operated in our clinic were included. Patients' serum thyroid hormone, anti-thyroglobuline (anti-TG) and anti-thyroid peroxidase (anti-TPO) levels and tumors' prognostic parameters (tumor size, axillary involvement, histological grade, lymphovascular invasion, receptor status, Ki-67 proliferation index) were collected. The correlation between serum thyroid autoantibody levels and tumor's prognostic factors were studied. Results: The prevalence of thyroid autoimmunity (high levels of serum anti-TPO and/or anti-TG) was 18.5% (n=37). Patients with thyroid autoimmunity had a significant lower rate of axillary involvement and a lower rate of Ki-67 proliferation index (22% vs. 46%[p=0,007] and 12.73% vs. 20.72% [p=0.025], respectively) and were more commonly included to the low-risk group (<14%) according to their Ki-67 scores (68% vs. 46%; p=0.015). Other parameters did not differ between the two groups. Conclusion: We found a favorable correlation between thyroid autoimmunity and axillary involvement and also Ki-67 proliferation index score, which are two crucial and strongly predictive parameters of breast cancer prognoses. This supports the idea of thyroid autoimmunity being a favorable prognostic parameter. Further studies are necessary to investigate the reasons of protective or predictive effect of high thyroid peroxidase levels in breast cancer patients.
Keywords: Breast cancer; autoimmune thyroid disease; prognostic factors; PREDICTIVE-VALUE; UNITED-STATES; METAANALYSIS; PROLIFERATION; ANTIBODIES; SURVIVAL; WOMEN; KI-67